IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PAI DALAM MENINGKATKAN POLA BERFIKIR SISWA DI SMP AN NURMANIYAH - Ahmad Masruri; Putri Ranita (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2025)
This research aims to examine, analyze and interpret the description of the implementation of the independent learning curriculum on student achievement at An-Nurmaniyah Junior High School, Ciledug. The research method used is qualitative by examining the learning outcomes of class VII students in Islamic Religious Education subjects with data collection methods also carried out by documentation, interviews and observation. The results of this research show that the achievements of An-Nurmaniyah Ciledug Middle School students with the independent curriculum do not only refer to the learning process but are also supplemented by the Pancasila Student Profile Strengthening Project, which is an independent curriculum program that strengthens various competencies in the Pancasila student profile. These things are interrelated and are supporting factors in increasing student achievement in the implementation of the independent learning curriculum at An-Nurmaniyah Junior High School, Ciledug.